ショウワ キチ フキン デノ 1984-85 ネン ノ ハンショク キ ニ オケル アデリーペンギン ノ コタイ グン チョウサ ト ヒョウシキ ズケ ノ カイキ リツ ニ オヨボス エイキョウ - 石川, 慎吾; イシカワ, シンゴ; 松田, 治; マツダ, オサム; 川口, 弘一; カワグチ, コウイチ; Ishikawa, Shingo; Matsuda, Osamu; Kawaguchi, Kouichi (1988)
P(論文) 第25次南極地域観測隊の生物環境モニタリング計画の一つとして, 東南極のプリンスオラフ海岸および宗谷海岸にあるアデリーペンギンの集団営巣地の個体群の計数を行った。全体的にみて, 過去4年間では個体数の大きな変動は見られなかったが, 袋浦, 水くぐり浦およびオングルカルベンの各集団営巣地では, 1983-84年の繁殖期には前年の約2/3-1/2に減少し, 1984-85年に再び回復するという変動が見られた。オングルカルベンおよび豆島の集団営巣地では, 1982-83年の繁殖期にフリッパーバンドによって標識された個体の回帰率と, 他の集団営巣地への移動を調べた。その結果, オングルカルベンでは, 1983-84年の回帰率よりも, 1984-85年のそれの方が高く, 1983-84年に帰巣した個体の91%は1984-85年にも帰巣していた。これは標識をつける時の人為的かく乱が回帰率に影響したものと考えられる。 Population census on the Adelie penguin in the 1984-85 breeding season on the Prince Olav Coast and the Soya Coast, East Antarctica was carried out as part of the biological monitoring programs of the 25th Japanese Antarctic Research Expedition. The record of a newly found rookery in Meholmen is described. In most of the rookeries, the maximum numbers of the Adelie penguin populations did not show heavy fluctuations during the last four seasons, though in some rookeries such as Hukuro Cove, Mizukuguri Cove and Ongulkalven, the population sizes fluctuated between the range of the largest size to one-half size of that. In the Ongulkalven and Mame-zima Island rookeries, the recovery rate and migration to other rookeries of banded penguins are discussed. departmental bulletin paper